The Role of International law in Addressing Climate Change: Legal Perspective and Policy Solution - Taqiyuddin kadir; T Saiful Basri; Ratih Dheviena Puru Hitaningtyas (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Climate change is one of the most significant challenges facing the world today. International law has a crucial role to play in addressing these issues through legal and policy frameworks. This study aims to analyze the role of international law in addressing climate change from a legal perspective and find effective policy solutions. The method used is a literature review with analysis of international legal documents and related policies, as well as case studies of policy implementation in several countries. The results show that although there have been some advances in international legislation and policy, there are still many challenges in its implementation that require innovative and collaborative solutions. The study also identified several policy solutions that could be improved through closer international cooperation, including harmonization of emission standards and more effective funding mechanisms. The recommendations of this study are expected to contribute to policymakers, legal practitioners, and other relevant parties in increasing the effectiveness of international law as a tool to address climate change.